MANAJEMEN PENDIDIKAN AL QUR’AN BERBASIS MASJID DALAM RAMADHAN KAMP (Study Kasus Masjid Nurul Huda Tarebung Kecamatan Gayam Sumenep) - Hartono Hartono (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2020)
The purpose of this research and community service is to provide understanding of the Qur'an and religious knowledge through instant Islamic boarding schools. The method used in this activity is Islamic boarding school-based religious learning in collaboration with mosque youth. Pesantren-based education has existed since the Prophet Muhammad